Methodological aspects of dietary quality assessment in Brazil: systematic review - Morais, Dayane de Castro; Moraes, Luís Fernando de Sousa; Silva, Danielle Cristina Guimarães da; Pinto, Carina Aparecida; Novaes, Juliana Farias de (Ciência & Saúde Coletiva, 2016)
This systematic review analyzes the methodologies of Brazilian studies that have used indices to evaluate dietary quality. A systematic search was performed of electronic databases (Lilacs, Medline, SciELO and Scopus) with no restriction on the year of publication of the studies. Original, Brazilian articles were selected that assessed dietary quality using the Healthy Eat- ing Index (HEI) or its revised versions. The descriptors were as follows: dietary quality; healthy eating index; and dietary quality index. Atotal of 45 articles were selected, of which 60% analyzed dietary quality using an instrument called the Healthy Eating Index and the rest used an index of dietary quality. Of the analyzed studies, 68.9% classified dietary quality. Most of the studies used ten items to evaluate dietary quality and were not standardized regarding methodologies. A total of 33.3% of the studies related the index to socioeconomic and demographic factors, food items and health conditions. Differences in terms of nomenclature and methodologies made it difficult to compare these studies of dietary quality.
Keywords: Dietary quality; Healthy eating index; Dietary quality index